2018
DOI: 10.1371/journal.pone.0206528
|View full text |Cite
|
Sign up to set email alerts
|

Threshold-varying integrate-and-fire model reproduces distributions of spontaneous blink intervals

Abstract: Spontaneous blinking is one of the most frequent human behaviours. While attentionally guided blinking may benefit human survival, the function of spontaneous frequent blinking in cognitive processes is poorly understood. To model human spontaneous blinking, we proposed a leaky integrate-and-fire model with a variable threshold which is assumed to represent physiological fluctuations during cognitive tasks. The proposed model is capable of reproducing bimodal, normal, and widespread peak-less distributions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The range of the total number of blinks was 13 to 166 (SD = 41.69, Mean = 68.95, Median = 68) for the multiplication videos and that was 31 to 270 (SD = 60.01, Mean = 122.3, Median = 127.5) for the differentiation video. Likewise the previous studies [1314], the total number of blinks in this paper demonstrated substantial individual differences. Moreover, simple counts of blinking could not detect the understanding level ( z = −1.73, p = 0.08 for the multiplication videos; z = −1.31, p = 0.19 the differentiation videos).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The range of the total number of blinks was 13 to 166 (SD = 41.69, Mean = 68.95, Median = 68) for the multiplication videos and that was 31 to 270 (SD = 60.01, Mean = 122.3, Median = 127.5) for the differentiation video. Likewise the previous studies [1314], the total number of blinks in this paper demonstrated substantial individual differences. Moreover, simple counts of blinking could not detect the understanding level ( z = −1.73, p = 0.08 for the multiplication videos; z = −1.31, p = 0.19 the differentiation videos).…”
Section: Resultssupporting
confidence: 83%
“…Human blinking characteristics have large interindividual variability [14, 17]. This has been a problematic fact for many researchers from early empirical studies [20] to current days [11,13]. The individual-based criteria proposed in this paper would be one of the resolutions for psychological phenomenon being problematic because of its large interindividual variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there may be a relation to eye physiology. 44 For example, after prolonged eyeblink suppression, the probability of eyeblink generation could be higher owing to eye-surface irritation. As a result, eyeblinks might synchronize more after suppression than in our model.…”
Section: Discussionmentioning
confidence: 99%